Intention to Use Mobile Payment System by Ethnicity: A Partial Least Squares Multi-group Approach - Tan, Kim Lim; Memon, A.; Sim, P.; Leong, C.; Soetrisno, F.; Hussain, K. (2019)
With recent developments in communication technologies, mobile payment (Mpayment) systems have gained popularity as a method to facilitate payment transactions. Despite that, the intention of adopting M-payment in the developing market as well as the implication of ethnicity in the context of developing countries remains largely unanswered. Following the theory of planned behaviour, this study examines the effects of attitude, subjective norm and perceived behavioural control on intention towards the use of an M-payment system among Malays and Chinese in Malaysia. Beliefs are included as antecedent variables so as to enhance understanding of the subject matter. Data was collected from 311 respondents. The partial least squares structural equation modelling (PLS-SEM) was employed to assess the research model. The moderating effect of ethnicity was tested by using a multi-group approach (MGA) from two subsamples (i.e., Chinese and Malays). Results highlight the need to understand the determinants to users’ intention towards M-payment systems in developing markets. It demonstrates the importance of knowing what is shared and what is not in multi-ethnic and multi-cultural countries like Malaysia. The results provide managerial implications into effective service operation and marketing of an M-payment system.